0116 Simulation audio improvement. (2nd November 2015) - Gay, Christopher; Graby, Matthew; Charlton, Olivia; Riby, Stuart
Abstract : Background/context: HILS's current video feedback system (SMOTS) integrates 16 cameras and 24 sounds feeds. Although versatility of the system is adequate, there are improvements to be made in the management of audio. There is evidence 1 to suggest that audio is as important, if not more so than video. HILS have worked with Scotia and Shure to integrate an upgraded audio system which will enhance simulation participation. Description of innovation or topic: The Shure Q-System manages audio in a way that allows different sound sources to be kept separate, rather than mixing into one inseparable stream. This has several benefits for simulation- Being able to tune out interference or unwanted Sound Dedicating an audio channel to SimMan 3G voice e to improve viewer's audio clarity Being able to 'zone in' on individual delegates within a scenario Improvements/outcomes (anticipated or recorded): All these improvements should result in the participants of simulation scenarios having an improved experience... Debriefers can feedback more accurately based on what candidates say Scenario viewers will be able to engage more with the scenario by hearing all elements of the scenario more clearly Technicians or faculty can control the 'soundscape' from an ipad, enabling a scalable range of options Pre-programmed audio settings for scenarios can allow the technician and/or simulation operator to focus more concentration on the scenario itself. Take home messages: Audio clarity can have huge impact on the engagement of simulation participants Systems exist that can be integrated into current AV solutions without conflicting Reference: http://vtrep.com/audio-is-more-important-than-video-picture-quality/